Predictors of Sexually Transmitted Infections among Female Sex Workers (FSWs) in a City of Northern India - Pallavi Shukla; Jamal Masood; J V Singh; V K Singh; Abhishek Gupta; Asuri Krishna (Wolters Kluwer Medknow Publications, 2015)
Introduction: Sexually transmitted infections (STIs) and Reproductive tract infections RTIs are important public health problems in India. The prevalence of these infections is considerably higher among high risk groups (HRGs) ranging from 20-30%. It is high time that a study should be conducted to explore different factors and conditions responsible for the practice of unsafe sex among female sex workers (FSWs) in Uttar Pradesh (UP) and the impact of this on social life and health of FSWs. As Lucknow provides a comprehensive opportunity in terms of tourism, occupation, and economy, it becomes a potential hub for sex work. Studying FSW in Lucknow can thus be considered as a yardstick for the entire FSW population of UP population. The present study was thus planned with the objective of knowing the STI prevalence and its determinants among FSWs. Materials and Methods: A cross-sectional descriptive study was conducted on FSWs registered with Targeted Intervention-Non-government Organization (TI-NGO), registered with Uttar Pradesh State Acquired Immuno Deficiency Syndrome (AIDS) Control Society (UPSACS) of Lucknow city. Total 288 subjects were studied. Results: The average age of FSWs was 31 years. FSWs were mostly Hindus and illiterate. The overall prevalence of STI as per Syndromic diagnosis was found to be 35.8%. However, the percentage of FSWs with STI was higher in street-based (50.6%) than home-based (29.8%). Majority (42.7%) of sex workers with STI had non-regular partners only while majority (52.4%) of sex workers without any STI had only regular partners. Condom usage with regular partners was poor. However, with the non-regular partners the condom usage was better. On multivariate analysis being single, having sex work as a sole means of earning, duration of sex work > 2 years, having pallor, and giving in to client's demand for unsafe sex were found to be significant in causing STI. Conclusions: Prevalence of STI among the female sex workers as per Syndromic diagnosis was found to be 35.8%. Unemployment, anemia, and having sex without condom for extra money, failure to persuade the client and not doing anything were found to be important predictors for presence of STI.